(untitled) (Experimental biology, 2015)
We have spent screening of 14 plant species on the ability to remediation of soils contaminated with organochlorine pesticides. It was found that due phytostabilization and phytoextraction plants reduced the concentration of organochlorine pesticides in the original soil to 28% of control. Keywords:.